Ubezpieczenia indywidualne minimalizujące skutki występowania zagrożeń - Filaber, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The essential role in the internal security system of the Republic of Poland shall be played by compulsory non-life insurances of economic nature. In particular, said insurances shall cover protection of each citizen against the peril of natural disasters.The current legal regulations of the insurance system against natural disasters, in particular with regard to the peril of flood in Poland, display imperfectionsand do not guarantee the adequate level of safety of an individual. Moreover, the system does not raise the citizens’ awareness of the need of securing their immovable properties against unpredictable consequences of the flooding peril and need of proper risk management in the face of advancing climate change and the decreasing protective role of a state.This paper attempts to answer the question, whether introducing asystem of general insurances could compensate the insured and the insurers for the liability for natural disasters risk management, which has been transferred upon them, and which is currently mitigated by asystem of voluntary insurances against the peril of flood. The paper also deals with the problem of the insufficient state aid in the case of emergency situation.
Keywords: individual insurences; security system; Poland; insurance system; risk